The impact of environmental subsidy on the performance of corporate environmental responsibility: Evidence from China - Chen, Guifu; Wei, Boyu; Zhu, Ruoran (Frontiers in Environmental Science, 2022)
Corporate environmental responsibility (CER) has become a critical factor for measuring the competitiveness of firms in China, and environmental subsidies may be a catalyst for promoting firms' CER. This study uses data from Chinese A-share listed firms during 2010–2020. Using the instrumental variable two-stage least squares (IV-2SLS) method, we found that environmental subsidies significantly improve corporate environmental performance but have no significant impact on the disclosure and governance of pollution emissions. We find that environmental subsidies are better for chemical and energy firms with high pollution levels, provide incentives for non-state-owned firms to improve CER and that their effect in western and eastern China is better than that in the central region. We also found that corporate social responsibility plays a moderating role in environmental subsidies that affect CER. Finally, this study finds that environmental subsidies may crowd out corporate investments to improve environmental performance. Based on the above results, we provide the corresponding policy suggestions.